2013
DOI: 10.1007/s10620-013-2562-8
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing Factors of Hepatocellular Carcinoma Recurrence Following Complete Remission in Response to Transarterial Chemoembolization

Abstract: Early recurrences following CR by TACE may be due mainly to undetectable remaining tumors, whereas late recurrences may be caused by newly appearing tumors in patients with a background of advanced cirrhotic liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 26 publications
3
20
0
Order By: Relevance
“…The fi ndings of the present study demonstrated an inverse association between tumor number and DFS time following initial TACE. Consistent with the present study, several previous studies have identified tumor number as a predictor of intrahepatic recurrence following initial TACE for HCC (27)(28)(29)(30)(31). Recurrence following initial remission by TACE has been more often reported in patients with multinodular-type HCC and with portal vein thrombosis (32).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The fi ndings of the present study demonstrated an inverse association between tumor number and DFS time following initial TACE. Consistent with the present study, several previous studies have identified tumor number as a predictor of intrahepatic recurrence following initial TACE for HCC (27)(28)(29)(30)(31). Recurrence following initial remission by TACE has been more often reported in patients with multinodular-type HCC and with portal vein thrombosis (32).…”
Section: Discussionsupporting
confidence: 90%
“…The distribution of lipiodol uptake determined by tumor differentiation and the blood vessel network have been shown to affect the local recurrence rate and long-term outcome in patients with HCC (37,38). Furthermore, consistent with the present study, a previous study showed that local recurrence developed more frequently in patients with early recurrence (≤1 year) compared with those with late recurrence (>1 year) (27). These results indicated that early recurrence is associated with local recurrence arising from limitations of the radiological evaluation of tumor response, and remnant tumors can develop and be recognizable by imaging modalities over time.…”
Section: Discussionsupporting
confidence: 90%
“…Out of 32 patients without recurrence after CR, all except 1 survived during the follow up period (1 died of hepatic failure about 19 months after CR); in contrast, 1, 2 and 3 year survival rates of those with recurrence were 97%, 82% and 67%, respectively. (p = 0.003) In another study, recurred HCC was found in 169 patients (77%) out of 220 consecutive HCC patients who had achieved CR by TACE followed for a median period of 72 months (12). Thus, the recurrences of HCC are very common even after the achievement of CR by TACE, and the recurrences of HCC are closely associated with shorter survival periods compared with patients without recurrence after CR by TACE.…”
Section: Tcs22-02mentioning
confidence: 95%
“…In our recent study, among the recurred 169 HCCs, 91 (54%) were found adjacent to the primary sites which were considered as being controlled well by TACE; 61 (36%) at the other site separated from original tumors, 17 (10%) both. Early recurrences were found in 45 cases out of 169 patients (27%; local recurrences/Secondary tumors/ both = 28/13/4); late recurrence in the remaining 124 cases (73%; local recurrences/secondary tumors/both = 63/48/13) (12). Compared with those with radiofrequency ablation (RFA), HCC patients treated with TACE present local recurrences more frequently in cases who achieved CR.…”
Section: Tcs22-02mentioning
confidence: 98%
See 1 more Smart Citation